Learning styles of entry-level physiotherapy students. - Mountford H; Jones S; Tucker B (Advances in Physiotherapy, 2006)
This research was conducted to identify the learning styles of Australian physiotherapy students. The subject sample consisted of 206 students from the entry-level physiotherapy programs (Bachelor of Science [Physiotherapy] and Master of Physiotherapy) at Curtin University of Technology. Subjects were recruited from the first and fourth year of the Bachelor of Science (BSc) (Physiotherapy) program and first and second year of the Master of Physiotherapy (MPhysio) program. Three subject groups included: (i) first-year BSc students, (ii) fourth-year BSc students, and (iii) MPhysio students. All subjects completed the Honey & Mumford Learning Style Questionnaire (LSQ) and were classified as having one or more learning styles. The most frequently preferred learning styles were Reflector (26%), followed by Reflector/Theorist (17.2%), then Activist (16.7%). There were no differences in the preferred learning style in the three groups, or between genders. Most physiotherapy students in the entry-level programs preferred a learning style in which they combine reviewing and thinking skills, rather than experiencing or planning skills. Based on the findings of this study, educators in entry-level programs need to develop learning experiences that will enhance students' experiencing and planning skills.